TEACHERS’ MOTIVATIONAL STRATEGIES FOR ENHANCING SPEAKING PROFICIENCY AMONG ALGERIAN EFL LEARNERS - Tobbi, Saida (Armenian Folia Anglistika, 2025)
Since the 1990s, research on motivational strategies has shifted focus from a sociological perspective to an education-oriented approach, highlighting situational factors such as language courses and teachers. This study explores how English as a foreign language (EFL) teachers’ motivational strategies support learners in developing speaking proficiency. Adopting a mixed-methods approach, it integrates quantitative and qualitative data for a comprehensive analysis. The research involved 101 second-year English students at Batna 2 University, with a randomly selected sample of 62 students, alongside 12 experienced second-year teachers. Data were collected through separate questionnaires for students and teachers. The findings reveal that motivational strategies play a pivotal role in fostering EFL learners’ speaking proficiency. Both teachers and students emphasized the usefulness of strategies such as interactive activities, personalized feedback, and positive reinforcement. Teachers regularly implemented these strategies, particularly interactive grammar games and fluency-focused activities, while students highlighted the value of establishing rapport and maintaining a positive classroom atmosphere. This study underscores the importance of tailored motivational strategies in helping students improve their speaking skills in EFL contexts.